Spread and current distribution of the cassava mealybug, Phenacoccus manihoti (Homoptera: Pseudococcidae), in Zaire - Hennessey, R.D.; Neuenschwander, Peter; Muaka, T. (Informa UK Limited, 1990)
The cassava mealybug, Phenacoccus manihoti Mat.‐Ferr., spread in Zaire from foci at Kinshasa (1973), Mulandi (1978), and Goma (1982). It now occurs over an area of 560 000 km2, mainly in regions with a dry season of at least 90 days. Within these regions the pest occurs principally in areas having low green‐leaf biomass towards the end of the dry season. Mealybug populations reached catastrophic levels mostly during prolonged periods of drought. The exotic parasitoid Epidinocarsis lopezi (De Santis) has spread over 130000 km2 in western Zaire and southern Shaba, where no further mealybug outbreak has since been recorded.